Regulation of bursa immune response by velogenic NDV - Teo, Kristeen Ye Wen; Yeap, Swee Keong; Tan, Sheau Wei; Omar, Abdul Rahman; Ideris, Aini; Tan, Soon Guan; Mohammed Alitheen, Noorjahan Banu (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Newcastle disease virus (NDV) has been well characterised and classified. We have reported the differential regulation of cytokines/chemokines expression in spleen post-infected with genotype VII and VIII NDV. To further understand the regulation of adaptive immunity by these strains of NDV, we compared the viral load, cytokines expression and oxidative stress in bursa of infected chicken. Genotype VII IBS002 was recorded with higher viral load in bursa of infected chicken comparing to genotype VIII AF2240. Although both strains of NDV upregulated proinflammatory cytokines (IFN-ɣ, CXCLi2 and IL-18) expression and nitric oxide in bursa of infected chicken, level of upregulation was greater in the bursa of AF2240 infected chicken. These findings supporting the idea of acute infection by AF2240, which resulted to earlier mortality than chicken infected with IBS002.